Flexible control switching method for converter station in LCC-HVDC transmission system - Peng, Maolan; He, Xiaopeng; Xiao, Ran; Feng, Lei; Liao, Fangqun; Jiang, Wen (Frontiers in Electronics, 2025)
Line Commutated Converter based High Voltage Direct Current (LCC-HVDC) transmission technology has the advantages of high withstand voltage and large current capability and has been widely used in renewable energy transmission. However, the power intermittency and fluctuation of renewable energy sources (RESs) such as wind and solar power will result in complex and variable operating conditions of the AC power grid. A single converter control strategy is difficult to adapt to all operating conditions, affecting the safety and stability of the system. Therefore, this paper first establishes the state-space model of the LCC-HVDC system with renewable energy at the sending-end and analyzes the small-signal stability and stable operating range of the system under different control strategies. Then, based on the designed control switching principles, a flexible control switching method applicable to the LCC-HVDC system is proposed. This method can not only enhance the stability of the system, but also ensure a smooth switching between different control strategies with minimal disturbance to the system. Finally, a simulation model is built on the PSCAD/EMTDC platform to verify the feasibility of this flexible control switching method. The simulation results show that the disturbance during the control switching is relatively small, and the flexible control switching method can effectively ensure the stable operation of the LCC-HVDC system under different operating conditions.